Design Build Applications Determination Cost of Goods Sold Using Weighted Average Method At PT Gemah Ripah Loh Jinawi Industry - Lutfiyah Lutfiyah; Sri Hariani Eko Wulandari; Endra Rahmawati (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
PT Gemah Ripah Loh Jinawi Industry (GRLJI) is a fertilizer industry companywhich produced two types of products; natural phosphate and dolomite. The company had quite large business process in ordering the fertilizer products from customers, manufacturing raw materials until delivering the accomplished products to the customer back. However, accountingsystem of PT GRLJI there were problems when calculated the cost of goods sold such as; the manager or finance administration should waiting for data purchase recap, data production process from the production manager, and recapitulation from marketing result per month. So, it is made slow process of recording and reporting the sold goods calculation. sometimes it wasinaccurate calculation which could hamper the profit of company.From those problems, it is required an application to determinate the cost of sales with appropriate method based on the policy of company. And it also able to calculate then produced the report of goods sold quickly and automatically. Weighted Average Method (WAM) was a pricing method which existed in stocks valuation based on average price of goods in the final period.Based on the application trial result using synopsis data which known by the company with monthly periods, the data showed the value of cost production, the sell price and the cost of goods sold automatically. Besides, it could help the data process and the determine process of goods sold cost faster.Keywords: Weighted Average Method, Application, The Goods Sold cost